Collaborative innovation in public administration: Theoretical background and research trends of co-production and co-creation - Tina Jukić; Primož Pevcin; Jože Benčina; Mitja Dečman; Sanja Vrbek (Administrative Sciences, 2019)
This paper presents the results of the content analysis of 139 Web of Science papers focused on collaborative innovation with external stakeholders of public administration, specifically on co-production and co-creation. The analysis included papers published between 2009 and 2018 and was based on a coding scheme consisting of 12 parameters grouped into four groups: paper descriptors, financial support of the research, methodological framework, and co-creation characteristics. The results reveal a considerable increase in researchers' interest in co-production and co-creation in the context of public administration in the last few years. This is particularly the case in Northern and Western Europe, where Anglo-Saxon and Nordic administrative traditions dominate. Furthermore, the results show that co-creation is most often placed in the contexts of social policy and welfare, as well as health care. Over the selected period, research seldom addressed companies as a target group in the co-creation of public services - in comparison to citizens and internal users. More than three quarters of the papers observed were empirical and less than 20% were quantitative. In general, a lack of conceptual clarity was often identified through the interchangeable usage of the terms co-creation and co-creation and the low level of international comparison - the majority of the papers focused on case descriptions at a national level, even though collaborative innovation is strongly related to administrative traditions dominating in specific regions.
Keywords: 350; collaborative innovation; co-creation; co-production; content analysis; Web of Science